2015
DOI: 10.1088/0031-9155/60/3/1185
|View full text |Cite
|
Sign up to set email alerts
|

Passively scattered proton beam entrance dosimetry with a plastic scintillation detector

Abstract: We tested the feasibility of using plastic scintillation detectors (PSDs) for proton entrance dosimetry. A PSD built with BCF-12 scintillating fiber was used to measure the absolute entrance dose of a passively scattered proton beam for energies ranging from 140 MeV to 250 MeV, and for a range of spread out Bragg peak (SOBP) widths at 2 energies, to quantify the effect of ionization quenching on the response of the detector and to determine the necessity of Cerenkov radiation correction in proton beams. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…We found that the average under-response of the PSD attributable to ionization quenching was 7.8% ± 1.0%, similar to the results published by Wootton et al [11]. The under-response for each field is shown in Figure 3.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…We found that the average under-response of the PSD attributable to ionization quenching was 7.8% ± 1.0%, similar to the results published by Wootton et al [11]. The under-response for each field is shown in Figure 3.…”
Section: Resultssupporting
confidence: 89%
“…The snout position was set at 30 cm. It is important to note that in a previous study by Wootton et al comparing a PSD with a plane-parallel ionization chamber, a snout position of 45 cm was used, whereas we used 30 cm, as required for patient treatment fields [11]. Thus, the air gap was 15 cm larger in the previous study than in the present study.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations